2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696896
|View full text |Cite
|
Sign up to set email alerts
|

Lift generation of hummingbird wing models with flexible loosened membranes

Abstract: Hummingbirds are promising reference for small flying robots in terms of their excellent ability to hover. Wing kinematics and shape of a hovering hummingbird were measured with four high-speed video cameras. Four types of wing models consisting of carbon fiber rods and polymer membranes with the same planform as the hummingbird wing were fabricated. 1-degree-of-freedom (DOF) flapping experiments with the wing models were performed, where the wing deformation and vertical force (hereafter called 'lift') were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The three-dimensional dynamic wing morphing of living organisms may be inspirational in designing the wings for flapping-wing micro air vehicles (MAVs) [ 58 ]. For instance, in a series of a membranous MAV wing-flapping experiments, it was found that both the aerodynamic vertical force and the mechanical efficiency increase as the wing has the more similar outline to that of the hummingbird or the wing membrane is loosened to allow spanwise twist [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional dynamic wing morphing of living organisms may be inspirational in designing the wings for flapping-wing micro air vehicles (MAVs) [ 58 ]. For instance, in a series of a membranous MAV wing-flapping experiments, it was found that both the aerodynamic vertical force and the mechanical efficiency increase as the wing has the more similar outline to that of the hummingbird or the wing membrane is loosened to allow spanwise twist [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, scanning electron microscope (SEM) measurements of C. anna ’s wing showed a physical connection between neighbouring barbs [ 30 ], justifying the use of a rigid and non-porous material for the wing model in our experimental scheme presented below. It is also assumed that wing deformation is minimal [ 40 ] and does not play a significant role during the downstroke due to special feather arrangement, as opposed to during upstroke and wing reversal. Therefore, only the downstroke is analysed herein.…”
Section: Methodsmentioning
confidence: 99%
“…An example of the latter case are swift wings which can either be extended or swept, with swept wings less prone to structural failure (Lentink et al 2007). Hummingbird wings fold less during hovering flight, but do exhibit some folding during the upstroke (Tanaka et al 2013), and the degree of folding during both upstroke and downstroke changes with flight speed (Tobalske et al 2007). Wing folding can also enhance flight control by allowing transient changes to maintain flight stability, such as tucking the wings in response to turbulence (Reynolds et al 2014) or to navigate through clutter (Williams and Biewener 2015).…”
Section: Wing Shape and Aerodynamicsmentioning
confidence: 99%